Fabrication of micro- and nano-particles of drug (I) for pharmaceutical application - Goh, Boon Beng. (2010)
Many drugs are of very poor water solubility, so they tend to be eliminated from the gastrointestinal tract before they could be absorbed into the blood circulation, resulting in low